2016
DOI: 10.5539/ass.v12n3p14
|View full text |Cite
|
Sign up to set email alerts
|

Financial Hegemony, Diversification Strategies and the Firm Value of Top 30 FTSE Companies in Malaysia

Abstract: This study investigates the relationships between financial hegemony groups, global diversification strategies and firm value of the Malaysia's 30 largest companies listed in FTSE Bursa Malaysia Index Series during 2009 to 2012 period. We chose Malaysia as an ideal setting because the findings contribute to the phenomenon of the diversification-performance relationship in the Southeast Asian countries. We apply hegemony stability theory to explain the importance of financial hegemony groups in deciding interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Significant negative performance is also manifested when it is measured by stock returns (in 2013) when firm size is controlled by either total assets or its market value. These negative results are consistent with the class hegemony theory of director interlocks that was advanced by Bates (1975) and the empirical findings of Yusoff et al (2016) and Nam and An (2018).…”
Section: Discussion Of Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Significant negative performance is also manifested when it is measured by stock returns (in 2013) when firm size is controlled by either total assets or its market value. These negative results are consistent with the class hegemony theory of director interlocks that was advanced by Bates (1975) and the empirical findings of Yusoff et al (2016) and Nam and An (2018).…”
Section: Discussion Of Resultssupporting
confidence: 87%
“…Caiazza et al (2019) deemed interlocking directorates as an expression of hegemonic power exercised by the elites of a society. Applying this theory, Yusoff et al (2016) reported that financial hegemony negatively affects the financial value of the firm. Nam and An (2018) posited that interlocking directors opportunistically use a well-developed social network to maintain their influential position and ultimately adversely affect firm performance.…”
Section: Class Hegemony Theorymentioning
confidence: 99%